HOW DO ENGLISH TEACHERS PERCEIVE ON INNOVATIVE MEDIA? DESCRIPTIVE ANALYSIS AT SINTANG'S SENIOR HIGH SCHOOLS - Burhanudin Rais; Lailatus Sa'adah (STKIP Persada Khatulistiwa Sintang, 2022)
Innovative learning media is essential in supporting the classroom's English learning process. Its use can increase the students' motivation, which affects the absorption of the material being taught. However, many teachers idolized using only monotonous media for teaching English. Thus, by following this phenomenon, the researchers aim to analyze the use of innovative media in Sintang High School, West Kalimantan. This research is important to know the phenomena that can be the future suggestion to the stakeholder in using media in Sintang because there is no similar research conducted. The method that the researcher used was a qualitative method. Some English teachers from several Senior High Schools were selected based on the purposive sampling method, which is public schools in the district of Sintang. Researchers interviewed the teachers and the students to get the validity. From this interview, the researchers know that the innovative media is needed in English language teaching. It is supported by their teaching experience in using innovative media in the classification of ICT and non-ICT media. however, the use of innovative media in teaching has several obstacles, such as internet connection, teacher ability in using technology and teacher creativity to prepare the media.